2019
DOI: 10.35448/jrat.v12i1.5345
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penerapan Informasi Akuntansi Manajemen, Sistem Pengukuran Kinerja Dan Sistem Penghargaan Terhadap Kinerja Manajerial Pada Perusahaan Ritel Modern Di Kota Jambi

Abstract: This study aims to determine the effect of the application of accounting information, performance measurement systems and reward systems to managerial performance in modern retail companies in Jambi City. The number of samples used in this study amounted to 61 people. The research sample consisted of lower level managers (lower management) to top (top management). The results showed that the application of management accounting information had an effect on managerial performance, the performance measurement sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
0
1
2
Order By: Relevance
“…This research aligns with a study conducted by (Pamungkas, 2015;Murdijaningsih, 2017), which found that total quality management significantly positively affects managerial performance. This study's results differ from those of research (Hardini, 2018;Pradnyaningtias, 2019), which found that TQM does not affect managerial performance. Implementing a reward system has been found to substantially and favorably impact managers' performance within various Manufacturing Companies situated in the Nusantara Bonded Zone.…”
Section: Discussioncontrasting
confidence: 99%
“…This research aligns with a study conducted by (Pamungkas, 2015;Murdijaningsih, 2017), which found that total quality management significantly positively affects managerial performance. This study's results differ from those of research (Hardini, 2018;Pradnyaningtias, 2019), which found that TQM does not affect managerial performance. Implementing a reward system has been found to substantially and favorably impact managers' performance within various Manufacturing Companies situated in the Nusantara Bonded Zone.…”
Section: Discussioncontrasting
confidence: 99%
“…Temuan ini memvalidasi bahwa penerapan fitur-fitur sistem informasi akuntansi manajemen secara efektif dapat meningkatkan kinerja manajerial di PT Karya Hevea Indonesia. Penelitian ini sejalan dengan penelitian lain (Anwar & Nainggolan, 2023); (Nainggolan, 2023); (Harahap, 2021); (Islami, Q & Daud, 2021); (Kontesa & Siahaan, 2021); (Lubis & Syafira, 2021); (Afriantoni & Erwati, 2018); Herawaty, 2018); (Irawati & Ardianshah, 2018) akuntansi manajemen dan kinerja manajerial. Penelitian sebelumnya (Maharani, 2011) menunjukkan bahwa dalam situasi ketidakpastian lingkungan yang tinggi, fitur sistem informasi akuntansi manajemen tidak berdampak signifikan terhadap kinerja manajerial.…”
Section: Pengujian Hipotesisunclassified
“…Penelitian ini sejalan dengan penelitian yang dilakukan oleh (Kontesa & Siahaan, 2021), (Afriantoni & Erwati, 2018), (Islami, Q & Daud, 2021) (Irawati & 2018) dan (Herawaty, 2018) menujukkan bahwa sistem informasi akuntansi berpengaruh signifikan terhadap kinerja manajerial.…”
Section: Pengaruh Sistem Informasi Akuntansi Terhadap Kinerja Manajerialunclassified